Effects of Concentric and Eccentric Training on the Stiffness and Blood Circulation of the Patellar Tendon - Kubo, Keitaro; Yata, Hideaki (Sports Medicine International Open, 2017)
The aim of the present study was to investigate the effects of concentric (CON) and eccentric (ECC) training on stiffness and blood circulation of the tendon, and clarify whether relative changes in tendon stiffness are related to those in tendon blood circulation. 17 subjects were assigned to training (n=9) and control (n=8) groups. Training group completed 12 weeks of unilateral training program for knee extensors. They performed 5 sets of CON or ECC at 80% of 1RM with 10 repetitions. Before and after training, cross-sectional area, stiffness, hysteresis, blood volume, and oxygen saturation of the patellar tendon were measured. Oxygen saturation significantly increased with CON and ECC. Stiffness significantly increased with CON but not with ECC. Other measured variables did not change after training. Furthermore, the relative change in tendon stiffness did not correlate with that in blood volume or oxygen saturation. In control group, measured variables did not change after training. These results suggest that tendon stiffness increased after CON but not after ECC; however no significant differences in the changes observed in size and blood circulation of the tendon were found between 2 protocols. Furthermore, changes in tendon stiffness were not related to those in tendon blood circulation.